Synthesis of zeolite phases from combustion by-products - Kedsarin Pimraksa (2018)
Synthesis of zeolites from combustion by-products, including fly ash, bottom ash and rice husk ash, was studied. A molar ratio of SiO2/Al2O3of 1.5 was used for the syntheses. Refluxing and hydrothermal methods were also used for synthesis for comparison. The reaction temperatures of refluxing and hydrothermal methods were 100°C and 130°C, respectively. Sodalite, phillipsite-K, and zeolite P1 with analcime were obtained when fly ash, bottom ash and rice husk ash were used as starting materials, respectively. With rice husk ash as a starting material, zeolite P1 was produced. This result had advantages over previous studies as there was no prior activation required for the synthesis. The concentrations and types of alkaline used in the synthesis also determined the zeolite type. The different zeolites obtained from three systems were measured for specific surface area and pore size by using BET and Hg-porosimetry, respectively. Ammonium exchange capacities of the synthesised powders containing zeolites, sodalite, zeolite P1 and phillipsite-K were 38.5, 65.0 and 154.7 meq 100 g-1, respectively. © The Author(s) 2010.